Examination of Tertiary Education Opportunities among Genders in Gombe State. - Muhammad , Muhammad Bashir; Ahmed , Abdullahi; Musa, Abba Mohammed (Int'l Journal of Education Research and Scientific Development, 2024)
Societies define their customs, values and norms. They define roles and responsibilities to both genders. Some societies believe in the saying, what a man can do, a woman can do it, while others hold the opinion that males and females have unique abilities and hence, the society has special expectations on each gender. While some people may view tertiary education as a necessity to only males, others may see it as imperative to females too. This study sought to find out whether equal opportunities to tertiary education exist between males and females in Gombe State. The design for this research was Survey. The entire tertiary institutions of learning within Gombe State served as the population of the study from which purposive sampling technique was used in drawing the sample. The instruments for the data collection was a structured questionnaire named, Gender Opportunity to Tertiary Education Questionnaire (GOTTEQ). The data was analyzed using frequency counts and mean scores. The research revealed the chances given by government, parents and spouses to different genders for tertiary education. From the results of the study, government at all levels has provided the enabling environment for gender equity to tertiary education, but significant number of parents discriminated between genders in that regard. Recommendations were made as to how to overcome gender disparity in tertiary education opportunity where exists.